Cyclin E low molecular weight isoforms occur commonly in early-onset gastric cancer and independently predict survival. Issue 3 (27th February 2008) - Milne, A N A; Carvalho, R; Jansen, M; Kranenbarg, E K; van de Velde, C J H; Morsink, F M; Musler, A R; Weterman, M A J; Offerhaus, G J A
Abstract : Background: Post-translational cleavage of full-length cyclin E from the N-terminus can produce low molecular weight (LMW) isoforms of cyclin E containing the C-terminus only. Aim: To assess their presence in early-onset gastric cancer (EOGC), stump cancers and conventional gastric cancers and ascertain how they influence survival in EOGC. Methods: The expression of full-length and LMW isoforms of cyclin E in 330 gastric cancers, including early-onset gastric cancer (EOGC), stump cancer and conventional gastric cancer (>45 years old) was compared using antibodies targeted to the N- and C-terminals. Results: LMW isoforms were found in 35% of EOGCs, compared to 8% of conventional gastric cancers and 4% of stump cancers; their presence was visualised in cell lines using western blot analysis. In addition, C-terminal staining was a positive predictor of survival in EOGC. In contrast, no correlation with survival was found with the N-terminal antibody which detects only full-length cyclin E. Conclusion: EOGCs have a unique molecular phenotype and LMW isoforms of cyclin E may independently influence survival in EOGC.